PELAKSANAAN PROGRAM PELATIHAN DALAM UPAYA PENINGKATAN KINERJAKARYAWAN - Sri Ria Lestari; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Training program strives to develop the results it wants to achieve, for this it requiresemployees who have adequate knowledge and skills. So the company createda training program to improve the abilities and skills of its employees. The implementation of the training program does not only affect the way members of the organization act, but also howthey communicate, behave, behave at work and all of this will affect employee performance. If employees' abilities and skills are improved through training programs, their performanceat work will also increase. The purpose of this research is to see the relationship betweentraining and employee performance. The tool used in data collection isa questionnaire and in analyzing the data using descriptive analysis and correlation analysis.Where the results ofthis analysis obtained the conclusion that there is a relationship between training programson employee performance.